ICT SYSTEM DEVELOPMENT IN THE LEARNING PROCESS BASED “MERDEKA BELAJAR” IN IMPROVING THE QUALITY OF STUDENT LEARNING OUTCOMES REPORTS - Samiyanto Samiyanto; Ahmad Muhibbin; Sigit Haryanto (LPPM STMIK Pringsewu, 2023)
A good learning process is ideally able to follow the existing social dynamics, so there is a need for development in learning management. The initial exploration needed for teachers and students is the condition of ICT information systems in learning, the designed ICT systems development based on independent learning, and the quality of student learning outcomes reports. This research aims to develop an ICT information system for independent learning-based learning. This development had carried out to improve the quality of student learning outcomes reports. The research method is research and development (RD), which is a research method of developing web-based online learning management and testing the effectiveness of products. The research was conducted in Vocational High Schools. The subjects under study are teachers and students. Data collection uses observation, interview, and documentation methods. Based on the results of the study, it is known that this research develops media that can manage learning for teachers and students. Learning is managed online on a website, which includes teacher learning tools and student assignments. Learning tools that are managed for teachers include student attendance, lesson schedules, lesson materials, assignments and homework, practice questions, and midterm and end-of-semester questions. The learning tools that students can access in online learning management include subject matter, assignments, homework, practice questions, and midterm and end-of-semester questions. This application is not a medium for learning, but a medium used to support learning activities in the classroom, both online and outside the network.